A Study of Sporulation and Spore Germination in Two-Spored Yeasts - Grewal, Narinder Singh (My University, 1971)
Nuclear divisions during sporulation of 15 predominantly two-spored and 2 predominantly four-spored yeasts were followed by Giemsa staining and light microscopy. The number of nuclei present per ascus was related to the presence or absence of conjugation at the time of germination of the spores. Plating experiments and a modification of the Finder Slide technique were used to determine whether progeny cells that developed from single spores of 2 two-spored and one four-spored strain could sporulate. The ploidy of these yeasts at different stages of their life cycles was estimated by DNA extractions. The spores of the two-spored yeasts were very difficult to separate following removal of their ascus walls, and electron microscopy was employed in an attempt to account for this.
Keywords: sporulation; yeast; nuclear division; germination; Finder Slide technique; electron microscopy